Trade agreements for developing countries - Verbit, Gilbert P. (New York : London : Columbia University Press, 1969)
This book examines problems associated with trade agreement relationship among developing countries and to indicate ways in which that problem might be solve under the trade agreement act.
Includes bibliographical footnotes and index.
ne 22/01/2019
Loans
Keywords: Trade; Developing countries